2022
DOI: 10.3389/fphar.2021.772926
|View full text |Cite
|
Sign up to set email alerts
|

PBK Enhances Cellular Proliferation With Histone H3 Phosphorylation and Suppresses Migration and Invasion With CDH1 Stabilization in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most frequent gastrointestinal malignancies with high morbidity and mortality rates. Several biological markers for the prognostication of patient outcome of CRCs are available. Recently, our group identified two favorable factors for the survival of CRC patients: PDZ-binding kinase (PBK) and phospho-histone H3 (PHH3). Both showed a significant inverse association to pT stage. The aim of this study was to uncover the mechanism through which these cellular proliferation–ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Recently, our group revealed that higher expression of PHH3, which is expressed in late G2 and M phases, is associated with lower pT stage and favorable clinical outcome in CRC patients [ 4 ]. These observations were partly explained by our additional in vitro study in which PBK (also known as TOPK) was demonstrated to accelerate cellular proliferation with direct phosphorylation of HH3 (histone H3) along with the suppression CRC cell migration and invasion [ 33 ]. In the present study, SPATA18-high CRCs showed higher PHH3 counts and CCNA labeling indexes than SPATA18-low tumors with favorable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our group revealed that higher expression of PHH3, which is expressed in late G2 and M phases, is associated with lower pT stage and favorable clinical outcome in CRC patients [ 4 ]. These observations were partly explained by our additional in vitro study in which PBK (also known as TOPK) was demonstrated to accelerate cellular proliferation with direct phosphorylation of HH3 (histone H3) along with the suppression CRC cell migration and invasion [ 33 ]. In the present study, SPATA18-high CRCs showed higher PHH3 counts and CCNA labeling indexes than SPATA18-low tumors with favorable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…33 OTS514 and OTS964 have been reported to significantly suppress the growth and metastasis of a variety of human cancer cells. 31,32,[41][42][43] Besides, in pre-clinical models, OTS514 showed potent anti-myeloma activity. 43 In addition to these three TOPK inhibitors, our previous study also identified a novel TOPK inhibitor, paeonol, which is an active compound isolated from traditional Chinese herbs.…”
Section: Discussionmentioning
confidence: 98%
“…9 Furthermore, it has been reported that inhibiting TOPK by specific inhibitors, OTS514 and OTS964, effectively inhibits the proliferation of many tumour cells. [30][31][32][33] Clinical studies reported that the expression of TOPK was strongly associated with poor prognosis of cancer patients. [34][35][36] As a potential tumour marker, TOPK has attracted extensive attention from basic and clinical researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org PDZ-binding kinase (PBK) is a serine/threonine kinase belonging to the mitogen-activated protein kinase (MAPK) kinase (MAPKK) family (Sun et al, 2016). Previous studies have shown that PBK is highly trans-activated in various cancers including ovarian cancer (Ma et al, 2022), lymphoma (Wang et al, 2022), kidney cancer (Sun et al, 2022), and colon cancer (Koshino et al, 2022), which is a promising molecular target for cancer-targeted therapy. It is worth mentioning that Yang et al (2019) found that PBK was overexpressed in HCC and was associated with poor prognosis.…”
Section: Discussionmentioning
confidence: 99%